Composite current collector and preparation method and application thereof

By setting a metal embedded layer in the polymer base film layer of the composite fluid collector and adjusting the strength factor, the problem of insufficient tensile strength and peel strength of the composite fluid collector is solved, and a significant improvement in tensile strength relative to the base film is achieved, while maintaining the advantages of lightness and low square resistance.

CN119786619AActive Publication Date: 2025-04-08HUNAN ENERGY FRONTIERS NEW MATERIALS TECH CO LTD

Patent Information

Application Number
CN202411988336.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The tensile strength of the existing composite fluid collectors has not been significantly improved compared with the base film, and the peel strength needs to be further improved to adapt to various mechanical stresses in battery manufacturing and use.

Method used

By providing a metal embedding layer in the polymer base film layer, the strength factor of the composite fluid collector is regulated, so that it can form a composite fluid collector within a certain range. The method includes plasma treatment, electroless plating and electroplating of the polymer base film to form a metal embedded layer and a metal layer.

Benefits of technology

The tensile strength and peel strength of the composite fluid collector are significantly improved, which significantly improves the tensile strength of its relative to the base film, while maintaining the advantages of lightness and thinness and low resistance performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119786619A_ABST
    Figure CN119786619A_ABST
Patent Text Reader

Abstract

The invention relates to a composite current collector and a preparation method and application thereof. The composite current collector comprises a polymer-based film layer and a metal layer arranged on at least one surface of the polymer-based film layer, wherein the polymer-based film layer comprises a metal embedded layer in contact with the metal layer; and the strength factor # imgabs0 # of the composite current collector is # imgabs1 # and # imgabs2 #. The strength factor of the composite current collector is regulated and controlled within a certain range, so that the tensile strength of the composite current collector can be obviously improved relative to the tensile strength of a base film. In addition, the composite current collector provided by the invention also has good peel strength and low sheet resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electronic components, and more specifically, to a composite current collector and a preparation method and application thereof. Background Art

[0002] Composite current collector is a high-performance conductive material, usually composed of two layers of metal (such as copper) and a layer of polymer substrate (such as PET, PP, PI, etc.). As an alternative to electrolytic copper foil for lithium batteries, composite current collector has the characteristics of low cost, light weight, high safety performance, and high energy density, and is also widely used in flexible electronic devices, thin film capacitors, electromagnetic shielding and other fields.

[0003] Although the composite current collector performs well in many aspects, the peel strength and tensile strength between the metal layer and the base film still need to be further improved. Since the composite current collector is a composite structure, good peel strength is a basic requirement for it. During battery manufacturing and daily use, the composite current collector needs to withstand multiple forces such as internal electrolyte pressure and external mechanical impact, so the tensile strength of the composite current collector needs to be improved.

[0004] The tensile strength of the composite current collector is affected by the tensile strength of the base film itself and the composite process. Among them, the existing composite process is easy to damage the base film, so that the tensile strength of the composite current collector is not significantly improved relative to the base film, or even lower than the base film. If the tensile strength of the composite current collector is lower than that of the base film, it will have a negative impact on the yield of the product and may also affect the durability and safety of high-performance batteries.

[0005] Patent CN117497687A discloses a method for preparing a composite copper foil current collector. The copper layer sputtered by the magnetron sputtering process has poor bonding with the polymer base film, and the high temperature during the magnetron sputtering process will cause perforation and damage to the polymer base film, which in turn results in no significant improvement in the tensile strength of the composite copper foil current collector relative to the base film. Summary of the invention

[0006] The primary purpose of the present invention is to overcome the problem that the tensile strength of the above-mentioned existing composite current collector is not significantly improved relative to the base film and the peel strength of the composite current collector is further improved, and to provide a composite current collector.

[0007] A further object of the present invention is to provide a method for preparing a composite current collector.

[0008] A further object of the present invention is to provide an application of the composite current collector in preparing a negative electrode of a lithium ion battery.

[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0010] A composite current collector comprises a polymer-based film layer and a metal layer disposed on at least one surface of the polymer-based film layer, wherein the polymer-based film layer comprises a metal embedding layer in contact with the metal layer;

[0011] The strength factor of the composite current collector for Said

[0012] Wherein, D is the thickness of the metal layer, D0 is the thickness of the polymer base film layer, and d is the thickness of the metal embedding layer.

[0013] In the present invention, the thickness D of the metal layer, the thickness D0 of the polymer base film layer and the thickness d of the metal embedding layer have the same unit. The metal embedding layer refers to a layer in which polymer and metal coexist after the pores of the polymer base film in the polymer base film layer are embedded with metal. The thickness d of the metal embedding layer refers to the shortest distance from the copper embedded deepest in the polymer base film to the surface of the polymer base film layer.

[0014] The inventors of the present invention have found that by regulating the strength factor of the composite current collector within a certain range, the tensile strength of the composite current collector can be significantly improved relative to the tensile strength of the polymer base film. R0 is the tensile strength of the polymer base film. In addition, by regulating the strength factor, the composite current collector can also have good peel strength.

[0015] If the strength factor is too small or the metal embedding layer is not provided, the tensile strength of the composite current collector is not improved to a good extent relative to the tensile strength of the base film, and the peel strength of the composite current collector is also poor. The strength factor should not be too large either, because the advantage of the composite current collector in terms of lightness and thinness is one of the main reasons for its replacement of traditional metal foils (such as electrolytic copper foils). If the strength factor is too large, the thickness D of the metal layer will be too large, which will lead to the composite current collector no longer having the advantage of being light and thin, and the manufacturing cost is high, and it is no longer suitable to replace traditional metal foils.

[0016] In the present invention, the strength factor of the composite current collector is Specifically, it can be 0.3, 0.33, 0.37, 0.40, 0.47, 0.50, 0.56, 0.6, 0.7, 0.78, 0.80, 0.86, 0.90, 1.00, 1.07, 1.10, 1.15, 1.17 or 1.2.

[0017] Preferably, the strength factor of the composite current collector is for

[0018] More preferably, the strength factor of the composite current collector is for

[0019] Further preferably, the strength factor of the composite current collector is for

[0020] Optionally, the thickness of the metal layer is: 0.5 μm≤D≤1.5 μm.

[0021] Preferably, the thickness of the metal layer is: 1 μm≤D≤1.5 μm.

[0022] Optionally, the thickness of the polymer-based film layer is: 2 μm≤D0≤8 μm.

[0023] Preferably, the thickness of the polymer-based film layer is: 3 μm≤D0≤5 μm.

[0024] More preferably, the thickness of the polymer-based film layer is: 3 μm≤D0≤3.5 μm.

[0025] Optionally, the thickness of the metal embedded layer is: 0.1 μm≤d≤D0 / 2 μm, wherein “D0 / 2” refers to the value obtained by dividing the thickness D0 of the polymer base film layer by 2.

[0026] Preferably, the thickness of the metal embedding layer is: 0.1 μm≤d≤1.5 μm.

[0027] More preferably, the thickness of the metal embedded layer is: 0.5 μm≤d≤1.5 μm.

[0028] Optionally, the polymer material of the polymer-based film layer is at least one of polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate or polypropylene.

[0029] Optionally, the material of the metal layer is at least one of copper, copper alloy, nickel, nickel alloy, silver or silver alloy.

[0030] Optionally, the metal in the metal embedding layer is at least one of copper, copper alloy, nickel, nickel alloy, silver or silver alloy.

[0031] Optionally, there are two metal layers, which are respectively arranged on two surfaces of the polymer-based film layer.

[0032] Preferably, the porosity of the polymer base film of the polymer base film layer is 5 to 70%.

[0033] More preferably, the porosity of the polymer base film of the polymer base film layer is 20-50%.

[0034] More preferably, the porosity of the polymer-based membrane is 30-50%.

[0035] Optionally, the average pore diameter of the pores of the polymer-based membrane of the polymer-based membrane layer is 20 to 100 nm.

[0036] Optionally, the polymer base film of the polymer base film layer has a tensile strength of 200 to 380 MPa.

[0037] Preferably, the tensile strength of the polymer base film of the polymer base film layer is 210 to 360 MPa.

[0038] More preferably, the polymer base film of the polymer base film layer has a tensile strength of 320 to 360 MPa.

[0039] A method for preparing a composite current collector comprises the following steps:

[0040] S1. Plasma treatment, sensitization and activation treatment are performed on the polymer base film to obtain a pretreated polymer base film;

[0041] S2. The pretreated polymer base film is electrolessly plated to form a metal embedded layer in the polymer base film to obtain a metallized base film;

[0042] S3. Electroplating the metallized base film to form a metal layer, thereby obtaining the composite current collector.

[0043] By compounding the polymer base film and the metal layer by chemical plating + electroplating in the preparation method of the present invention, not only can a metal embedded layer be formed in the polymer base film, but the method of forming the metal embedded layer will not damage the polymer base film, thereby significantly improving the tensile strength of the composite current collector relative to the tensile strength of the base film, and at the same time improving the peel strength of the composite current collector. In addition, the preparation method of the present invention is not only applicable to polymer base films whose commonly used materials are PP and PET, but also applicable to polymer base films whose materials are PE.

[0044] Optionally, the porosity of the polymer-based membrane in step S1 is 5-70%, and specifically may be 5%, 10%, 20%, 30%, 40%, 50%, 60% or 70%.

[0045] Preferably, the porosity of the polymer-based membrane in step S1 is 20-50%.

[0046] More preferably, the porosity of the polymer-based membrane in step S1 is 30-50%.

[0047] Optionally, the average pore size of the voids of the polymer-based membrane in step S1 is 20 to 100 nm.

[0048] Optionally, the power of the plasma treatment in step S1 is 50 to 200 W, and the time is 60 to 300 s.

[0049] Optionally, the sensitizing solution used in the sensitization treatment in step S1 includes components with the following concentrations: SnCl2 5-25 g / L, HCl 10-35 ml / L.

[0050] Optionally, the sensitization treatment time in step S1 is 0.5 to 3 minutes.

[0051] Optionally, after the sensitization treatment in step S1 and before the activation treatment, a cleaning step is also included.

[0052] Optionally, the cleaning agent is water.

[0053] Optionally, the cleaning time is 5 to 15 seconds.

[0054] Optionally, the activation solution used in the activation treatment in step S1 includes the following components in concentration: PdCl2

[0055] 0.5~2g / L, HCl 8~20ml / L.

[0056] Optionally, the activation treatment time in step S1 is 0.5 to 3 minutes.

[0057] Optionally, the activation treatment in step S1 further includes a drying step.

[0058] Optionally, the chemical plating in step S2 may be performed once or twice.

[0059] Optionally, when the number of chemical plating is 1 time, the chemical plating solution includes components with the following concentrations: copper sulfate 5-10 g / L, disodium EDTA 30-60 g / L, bipyridine 5-20 mg / L, sodium hydroxide 3-8 g / L, formaldehyde 5-10 g / L; the chemical plating time is 6-8 min.

[0060] Preferably, when the number of chemical plating is 2 times, the chemical plating includes first chemical plating and second chemical plating in sequence; the chemical plating solution of the first chemical plating includes components with the following concentrations: copper sulfate 5-10 g / L, disodium EDTA 30-60 g / L, bipyridine 5-20 mg / L, sodium hydroxide 3-8 g / L, and formaldehyde 5-10 g / L; the chemical plating solution of the second chemical plating includes components with the following concentrations: copper sulfate 5-15 g / L, disodium EDTA 5-10 g / L, potassium sodium tartrate 20-40 g / L, bipyridine 5-20 mg / L, sodium hydroxide 5-10 g / L, and formaldehyde 5-20 g / L.

[0061] Compared with chemical plating performed once, chemical plating performed twice can achieve the same thickness of the metal embedding layer in a shorter time through the coordination of the first chemical plating and the second chemical plating, and is more efficient.

[0062] Optionally, the first chemical plating time is 1 to 3 minutes; the second chemical plating time is 1 to 2 minutes.

[0063] Optionally, the electroplating in step S2 is multi-stage electroplating.

[0064] Optionally, step S2 further includes a corrosion inhibition step after the electroplating.

[0065] Optionally, the corrosion inhibition treatment is carried out by immersing in a corrosion inhibition liquid.

[0066] Optionally, the immersion time of the corrosion inhibition solution is 2 to 5 minutes, and the temperature is 30 to 70°C.

[0067] Optionally, the corrosion inhibition solution used for immersion in the corrosion inhibition solution comprises components with the following concentrations: 5-20 mg / L BTA and 2-30 mg / L ammonium molybdate.

[0068] The application of the composite current collector in preparing the negative electrode of a lithium ion battery is also within the protection scope of the present invention.

[0069] Compared with the prior art, the present invention has the following beneficial effects:

[0070] (1) The present invention regulates the strength factor of the composite current collector within a certain range, which can significantly improve the tensile strength of the composite current collector relative to the tensile strength of the base film; at the same time, regulating the strength factor also enables the composite current collector to have good peel strength. In addition, the composite current collector of the present invention also has low square resistance.

[0071] (2) The polymer base film and the metal layer are composited by chemical plating + electroplating in the preparation method of the present invention, which can not only form a metal embedded layer in the polymer base film, but also the method of forming the metal embedded layer will not damage the polymer base film, thereby significantly improving the tensile strength of the composite current collector relative to the tensile strength of the base film, and at the same time improving the peel strength of the composite current collector. In addition, the preparation method of the present invention is not only applicable to the existing commonly used polymer base films made of PP and PET, but also applicable to polymer base films made of PE. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 Schematic diagram of the structure of the composite current collector of Example 2.

[0073] Figure 2 This is a SEM image of the surface of the composite current collector of Example 2.

[0074] Figure 3 This is a SEM image of the cross section of the composite current collector of Example 2. DETAILED DESCRIPTION

[0075] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0076] Example 1

[0077] The present embodiment provides a composite current collector, which includes a polymer-based film layer 1 and a metal layer 2 disposed on both surfaces of the polymer-based film layer 1, wherein the polymer-based film layer 1 includes a metal embedding layer 11 in contact with the metal layer. The thickness D0 of the polymer-based film layer 1 is 3 μm, the thickness D of the metal layer 2 is 1 μm, and the thickness d of the metal embedding layer 11 is 1.5 μm. The polymer material of the polymer-based film layer 1 is polyethylene, the material of the metal layer 2 is copper, the polymer material in the metal embedding layer 11 is polyethylene, and the metal in the metal embedding layer 11 is copper. The porosity of the polymer-based film of the polymer-based film layer 1 is 30%.

[0078] The preparation method of the composite current collector of this embodiment comprises the following steps:

[0079] 1) A PE film with a porosity of 30%, an average pore diameter of 80 nm, and a thickness of 3 μm is selected as a polymer base film, and the base film is first treated with low-pressure plasma, and then immersed in a prepared sensitizing solution for 2 minutes, and then washed in deionized water for 10 seconds. After washing, it is immersed in an activation solution for 2 minutes, and then dried at 60°C for 2 minutes to obtain a pretreated polymer base film. The conditions for plasma treatment are: power of 50 W, time of 80 seconds, and plasma treatment gas is argon; the composition of the sensitizing solution is: SnCl2 20 g / L, HCl30 ml / L, and the solvent is deionized water; the composition of the activation solution is: PdCl2 1.0 g / L, HCl10 ml / L, and the solvent is deionized water.

[0080] 2) Immerse the pretreated polymer base film in the first chemical plating solution for 3 minutes, stir the first chemical plating solution continuously during the immersion process, immerse it in the second chemical plating solution for 1 minute, stir the second chemical plating solution continuously during the immersion process, take it out, and obtain a metallized film. The first chemical plating solution is composed of: 6g / L copper sulfate, 50g / L disodium EDTA, 15mg / L bipyridyl, 6g / L sodium hydroxide, 5g / L formaldehyde, and the solvent is deionized water; the second chemical plating solution is composed of: 8g / L copper sulfate, 5g / L disodium EDTA, 40g / L potassium sodium tartrate, 10mg / L bipyridyl, 8g / L sodium hydroxide, 15g / L formaldehyde, and the solvent is deionized water.

[0081] 3) The metallized film is electroplated in multiple stages to form a metal layer with a thickness of 1 μm on both sides; then immersed in a corrosion inhibitor at 45°C for 2 minutes, washed with deionized water, and dried with hot air at 60°C to obtain a composite current collector. The corrosion inhibitor is composed of: BTA 10 mg / L, ammonium molybdate 15 mg / L, and the solvent is deionized water.

[0082] Embodiments 2 to 5

[0083] The difference between the composite current collectors of Examples 2 to 5 and the composite current collector of Example 1 is that the thickness d of the metal embedding layer 11 is different, as shown in Table 1. Figure 1 shown.

[0084] The preparation method of the composite current collector of Examples 2 to 5 is different from that of the composite current collector of Example 1 in that the immersion time of the first chemical plating solution and the second chemical plating solution in step 2) is different. The immersion time of the first chemical plating solution of Examples 2 to 5 is 2.5 min, 2 min, 1.6 min and 1.0 min, respectively, and the immersion time of the second chemical plating solution of Examples 2 to 5 is 1.25 min, 1.5 min, 1.7 min and 2.0 min, respectively.

[0085] Embodiment 6-7

[0086] The composite current collectors of Examples 6 to 7 are different from the composite current collector of Example 3 in that the porosity of the polymer base film of the polymer base film layer 1 is different, as shown in Table 1 for details.

[0087] The preparation methods of the composite current collectors of Examples 6 to 7 are different from the preparation method of the composite current collector of Example 3 in that: in step 1), the porosity of the selected PE membranes is 20% and 50%, respectively.

[0088] Embodiments 8 to 9

[0089] The difference between the composite current collectors of Examples 8 to 9 and the composite current collector of Example 1 is that the thickness D of the metal layer 2 is different, as shown in Table 1 for details.

[0090] The method for preparing the composite current collector of Example 8 differs from the method for preparing the composite current collector of Example 1 in that: in step 3), the thickness of the metal layer formed on both sides of the metallized film is 1.2 μm by controlling the time of multiple electroplating stages.

[0091] The method for preparing the composite current collector of Example 9 is different from that of Example 1 in that: in step 3), the thickness of the metal layer formed on both sides of the metallized film is 1.5 μm by controlling the time of multiple electroplating stages.

[0092] Embodiments 10 to 11

[0093] The difference between the composite current collectors of Examples 10 to 11 and the composite current collector of Example 1 is that the thickness D0 of the polymer base film layer 1 is different, as shown in Table 1 for details.

[0094] The difference between the preparation methods of the composite current collectors of Examples 10 to 11 and the preparation method of the composite current collector of Example 1 is that in step 1), the thickness of the selected PE films are 3.5 μm and 4.5 μm, respectively.

[0095] Comparative Example 1

[0096] The composite current collector of Comparative Example 1 is different from the composite current collector of Example 1 in that the thickness D0 of the polymer-based film layer 1 and the thickness d of the metal embedded layer 11 are different, as shown in Table 1 for details.

[0097] The preparation method of the composite current collector of Comparative Example 1 is different from that of Example 1 in that: in step 1), the thickness of the selected PE film is 4.5 μm; in step 2), it is not immersed in the first chemical plating solution, but only immersed in the second chemical plating solution, and the immersion time is 2.5 min.

[0098] Comparative Example 2

[0099] The composite current collector of Comparative Example 2 is different from the composite current collector of Example 1 in that the thickness D0 of the polymer base film layer 1, the thickness D of the metal layer 2 and the thickness d of the metal embedded layer 11 are different, as shown in Table 1 for details.

[0100] The preparation method of the composite current collector of comparative example 2 is different from that of the composite current collector of embodiment 1 in that: in step 1), the thickness of the selected PE film is 2.5 μm; in step 2), the process of chemical plating is: the pretreated base film is immersed in the first chemical plating solution for 3 minutes, and then immersed in the second chemical plating solution for 1 minute. In step 3), by controlling the time of multiple electroplating stages, the thickness of the metal layer formed on both sides is 2 μm.

[0101] Comparative Example 3

[0102] The composite current collector of Comparative Example 3 is different from the composite current collector of Example 1 in that the metal embedding layer 11 is not provided, that is, the thickness d of the metal embedding layer 11 is 0, and the porosity of the polymer base film of the polymer base film layer 1 is different, as shown in Table 1 for details.

[0103] The preparation method of the composite current collector of Comparative Example 3 is different from that of the composite current collector of Example 1 in that: in step 1), the porosity of the selected PE film is 0.

[0104] Sample characterization and performance testing

[0105] 1. Cross-section and surface morphology

[0106] The images were taken using a scanning electron microscope (SEM). In the SEM test, the surface and cross-sectional morphology were tested after the gold spraying treatment. The gold spraying is to improve the conductivity of the sample to obtain a clear image. The gold-plated film formed by the gold spraying is about 10 to 30 nm and will not affect the observation of the morphology. In addition, the images need to be taken under low voltage conditions to avoid burning the base film material. Among them, the surface and cross-sectional morphology of the composite current collector of Example 2 are as follows: Figure 2 and Figure 3 As shown. Figure 2 It can be seen that the metal embedding layer and the metal layer are formed by the chemical plating + electroplating method of the present invention without damaging the polymer base film, which is conducive to significantly improving the tensile strength of the obtained composite current collector compared to the polymer base film. Figure 3 It can be seen that by adopting the chemical plating method of the present invention, a metal embedding layer can be formed on the base film. The formation of the metal embedding layer is conducive to significantly improving the tensile strength of the obtained composite current collector compared with the polymer base film.

[0107] 2. Thickness

[0108] Through SEM cross-sectional analysis, the thickness of the polymer base film layer (D0), the thickness of the metal embedded layer (d), and the thickness of the metal layer (D) can be directly measured, as shown in Table 1. The thickness d of the metal embedded layer refers to the shortest distance from the deepest copper embedded in the polymer base film to the surface of the polymer base film layer.

[0109] 3. Tensile strength

[0110] The polymer-based films and composite current collectors of the embodiments and comparative examples were subjected to tensile strength tests using a Shimadzu electronic universal testing machine AGS-X-10kN tensile tester, with a sample length of 150 mm*15 mm, a test spacing of 8 mm, and a tensile speed of 50 mm / min.

[0111] 4. Peel strength

[0112] Test the peel strength of the composite current collector of each embodiment and comparative example. Cut the prepared flat composite current collector sample into a sample with a width of 24 mm and a length of 300 mm, fold the adhesive surface of one end of the cut sample to form a folded layer of about 12 mm long; stick the other end of the sample to one end of the steel plate, and roll it twice at a speed of 600 mm / min with an adhesive tape roller, then place it in an electronic peel tester, set the test speed to 250 mm / min, and the sample width to 24 mm; the equipment automatically records the force value during the peeling process and reports the peel strength of the sample accordingly.

[0113] 5. Square resistance test

[0114] The square resistance of the composite current collector of each embodiment and comparative example was tested. A four-probe tester was used to set the correction coefficient according to the test requirements; after selecting the measurement category, the instrument was switched to the measurement mode; the sample was placed on the test bench, the probe was pressed down to make good contact with the sample, and the test result was read.

[0115] The results of sample characterization and performance testing are shown in Table 1 below.

[0116] Table 1

[0117]

[0118] In Table 1: R0 is the tensile strength of the polymer base film, in MPa. The units of D0, D and d are all μm. is the intensity factor, Dimensionless unit. R m is the tensile strength of the composite current collector, in MPa. X is the degree of improvement of the tensile strength of the composite current collector relative to the tensile strength of the base film, and the calculation process is X = ((R m -R0) / R0)*100%. The unit of peel strength is N / m. The unit of square resistance is mΩ / □.

[0119] From Table 1, we can see that:

[0120] The tensile strength of the composite current collectors of Examples 1 to 11 is increased by more than 9.7% relative to the tensile strength of the base film, which indicates that the strength factor of the composite current collector can be adjusted. Within a certain range, the tensile strength of the composite current collector can be significantly improved relative to the tensile strength of the polymer base film; at the same time, the peel strength of the composite current collectors of Examples 1 to 11 is above 550 N / m, indicating that the strength factor of the composite current collector can be regulated to make the composite current collector have good peel strength. Within a certain range, the composite current collector can also have a low square resistance (all below 17mΩ / □).

[0121] Comparing Examples 1 to 5, it can be seen that as d increases, the tensile strength of the composite current collector relative to the tensile strength of the base film gradually increases, the tensile strength and peel strength of the composite current collector gradually increase, and the square resistance gradually decreases. Among them, the square resistance of Example 1 decreases significantly compared with Examples 2 to 5, which is caused by the interconnection of the metal embedded layers on both sides of the base film of Example 1.

[0122] Comparing Example 3 and Examples 6 to 7, it can be seen that as the porosity of the base film increases, the strength factor It first increases and then decreases, and the degree of improvement in the tensile strength of the composite current collector relative to the tensile strength of the base film also first increases and then decreases.

[0123] Comparing Examples 1, 8 and 9, it can be seen that as the thickness of the metal layer increases, the intensity factor Gradually improves, the degree of improvement of the tensile strength of the composite current collector relative to the tensile strength of the base film gradually increases, the tensile strength of the composite current collector is improved, and the square resistance performance is reduced.

[0124] By comparing Examples 1, 10 and 11, it can be seen that as the thickness of the base film (polymer base film layer) increases, the degree of improvement of the tensile strength of the composite current collector relative to the tensile strength of the base film gradually decreases, and the tensile strength and square resistance of the composite current collector gradually increase.

[0125] The strength factor of Comparative Example 1 was not controlled within an appropriate range, the tensile strength of the composite current collector was not improved well relative to the tensile strength of the base film, and the peel strength of the composite current collector was insufficient.

[0126] The strength factor of Comparative Example 2 is too large. Although the tensile strength of the composite current collector is greatly improved relative to the tensile strength of the base film, the thickness of the metal layer is too large, which results in the composite current collector no longer having the advantage of being thin and light, and the manufacturing cost is high, and it is no longer suitable to replace traditional metal foils (such as electrolytic copper foil).

[0127] The composite current collector of Comparative Example 3 does not have a metal embedding layer, and the tensile strength of the composite current collector is only slightly improved relative to the tensile strength of the base film; and its peel strength is obviously insufficient, which does not meet the requirements in the industry.

[0128] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A composite current collector, characterized in that: The invention comprises a polymer-based film layer and a metal layer disposed on at least one surface of the polymer-based film layer, wherein the polymer-based film layer comprises a metal embedded layer in contact with the metal layer; The strength factor of the composite current collector for Said Wherein, D is the thickness of the metal layer, D0 is the thickness of the polymer base film layer, and d is the thickness of the metal embedding layer.

2. The composite current collector according to claim 1, characterized in that: The strength factor of the composite current collector for 3. The composite current collector according to claim 2, characterized in that: The strength factor of the composite current collector for 4. The composite current collector according to claim 3, characterized in that: The strength factor of the composite current collector for 5. The composite current collector according to claim 1, characterized in that: The thickness of the metal layer is: 0.5 μm≤D≤1.5 μm.

6. The composite current collector according to claim 5, characterized in that: The thickness of the metal layer is: 1.0 μm≤D≤1.5 μm.

7. The composite current collector according to claim 1, characterized in that: The thickness of the polymer base film layer is: 2 μm≤D0≤8 μm.

8. The composite current collector according to claim 7, characterized in that: The thickness of the polymer-based film layer is: 3 μm≤D0≤3.5 μm.

9. The composite current collector according to claim 1, characterized in that: The thickness of the metal embedding layer is: 0.1 μm≤d≤D0 / 2 μm.

10. The composite current collector according to claim 9, characterized in that: The thickness of the metal embedded layer is: 0.1 μm≤d≤1.5 μm.

11. The composite current collector according to claim 1, characterized in that: The polymer material of the polymer-based film layer is at least one of polyethylene, polypropylene, polystyrene, polyethylene terephthalate, polybutylene terephthalate or polypropylene.

12. The composite current collector according to claim 1, characterized in that: The material of the metal layer is at least one of copper, copper alloy, nickel, nickel alloy, silver or silver alloy.

13. The composite current collector according to claim 1, characterized in that: The metal in the metal embedding layer is at least one of copper, copper alloy, nickel, nickel alloy, silver or silver alloy.

14. The composite current collector according to claim 1, characterized in that: The number of the metal layers is two, which are respectively arranged on two surfaces of the polymer-based film layer.

15. The composite current collector according to claim 1, characterized in that: The porosity of the polymer base film of the polymer base film layer is 5-70%.

16. The composite current collector according to claim 15, characterized in that: The porosity of the polymer base film of the polymer base film layer is 20-50%.

17. The composite current collector according to claim 1, characterized in that: The average pore size of the voids of the polymer base film of the polymer base film layer is 20 to 100 nm.

18. A method for preparing a composite current collector, characterized in that: The steps include: S1. Plasma treatment, sensitization and activation treatment are performed on the polymer base film to obtain a pretreated polymer base film; S2. The pretreated polymer base film is electrolessly plated to form a metal embedded layer in the polymer base film to obtain a metallized base film; S3. Electroplating the metallized base film to form a metal layer, thereby obtaining the composite current collector.

19. The preparation method according to claim 18, characterized in that: The power of the plasma treatment in step S1 is 50 to 200 W, and the time is 60 to 300 s.

20. The preparation method according to claim 18, characterized in that: The sensitizing solution used in the sensitization treatment in step S1 includes the following components in concentration: SnCl2 5-25 g / L, HCl 10-35 ml / L.

21. The preparation method according to claim 18 or 20, characterized in that: The sensitization treatment time in step S1 is 0.5 to 3 minutes.

22. The preparation method according to claim 18, characterized in that: The activation solution used in the activation treatment in step S1 includes the following components in concentration: PdCl2 0.5-2 g / L, HCl 8-20 ml / L.

23. The preparation method according to claim 18 or 22, characterized in that: The activation treatment time in step S1 is 0.5 to 3 minutes.

24. The preparation method according to claim 18, characterized in that: The number of times of chemical plating in step S2 can be once or twice.

25. The preparation method according to claim 24, characterized in that: When the number of chemical plating is 1 time, the chemical plating solution includes the following components in concentration: copper sulfate 5-10g / L, disodium EDTA 30-60g / L, bipyridine 5-20mg / L, sodium hydroxide 3-8g / L, formaldehyde 5-10g / L; the time of chemical plating is 6-8min.

26. The preparation method according to claim 24, characterized in that: When the number of chemical plating is 2 times, the chemical plating includes first chemical plating and second chemical plating in sequence; the chemical plating solution of the first chemical plating includes components with the following concentrations: 5-10 g / L copper sulfate, 30-60 g / L disodium EDTA, 5-20 mg / L bipyridine, 3-8 g / L sodium hydroxide, and 5-10 g / L formaldehyde; the chemical plating solution of the second chemical plating includes components with the following concentrations: 5-15 g / L copper sulfate, 5-10 g / L disodium EDTA, 20-40 g / L potassium sodium tartrate, 5-20 mg / L bipyridine, 5-10 g / L sodium hydroxide, and 5-20 g / L formaldehyde.

27. The preparation method according to claim 26, characterized in that: The time of the first chemical plating is 1 to 3 minutes; the time of the second chemical plating is 1 to 2 minutes.

28. The preparation method according to claim 18, characterized in that: The method further comprises a corrosion inhibition step after the electroplating.

29. Use of the composite current collector according to any one of claims 1 to 17 in preparing a negative electrode for a lithium ion battery.

Citation Information

Patent Citations

  • Current collector, pole piece and battery

    CN111933953A

  • Preparation method and preparation device of composite current collector

    CN115440985A

  • Polymer-based radiation refrigeration film and preparation method thereof

    CN117283834A

  • Metallized polymer film with multilayer structure

    CN218593867U

  • Layered electronic device

    US20140054578A1

Cited By

  • Composite current collector, preparation method therefor and use thereof

    WO2026143796A1